2011
DOI: 10.1176/appi.neuropsych.23.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Structural Correlates of Response Perseveration in Individuals With Psychopathy

Abstract: Structural deficits in the frontotemporal network have been shown in individuals with psychopathy and are posited to contribute to neuropsychological impairments such as response perseveration. However, no study to date has examined structural correlates of response perseveration in individuals with psychopathy. In this structural MRI study, the authors found higher correlations between increased response perseveration and reduced cortical thickness in the orbitofrontal and anterior temporal regions in individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Boccardi et al, 2011; Tiihonen et al, 2008; de Oliveira-Souza, 2008), along with volume reductions in the most anterior frontopolar regions of the prefrontal cortex (Tiihonen et al, 2008; de Oliveira-Souza, 2008). It has also been reported that cortical thickness in the orbitofrontal region of psychopaths is inversely related to response perseveration—a classic behavioral correlate of psychopathy (Yang et al, 2011). These structural abnormalities closely parallel functional differences which have also been reported in prefrontal regions.…”
Section: Neuroimaging In Psychopathy: a Brief Reviewmentioning
confidence: 99%
“…Boccardi et al, 2011; Tiihonen et al, 2008; de Oliveira-Souza, 2008), along with volume reductions in the most anterior frontopolar regions of the prefrontal cortex (Tiihonen et al, 2008; de Oliveira-Souza, 2008). It has also been reported that cortical thickness in the orbitofrontal region of psychopaths is inversely related to response perseveration—a classic behavioral correlate of psychopathy (Yang et al, 2011). These structural abnormalities closely parallel functional differences which have also been reported in prefrontal regions.…”
Section: Neuroimaging In Psychopathy: a Brief Reviewmentioning
confidence: 99%
“…Reductions in orbitofrontal gray matter have been consistently observed in comparing psychopaths to non-psychopaths [52,60,61], along with reductions in the most anterior frontopolar regions of the prefrontal cortex [60,61]. It has also been reported that cortical thickness in the orbitofrontal region of psychopaths is inversely related to response perseveration, a classic behavioral correlate of psychopathy [62]. The orbitofrontal cortex of those with high psychopathic traits and criminal convictions shows reduced gray-matter volume and thickness compared to those without self-reported criminal convictions [50].…”
Section: Recent Neuroimaging and Psychopathymentioning
confidence: 99%
“…Reduced gray matter volumes have been reported in psychopaths’ amygdala and orbitofrontal cortex and cingulate cortex (Boccardi et al 2011; Yang and Raine 2009; Yang et al 2010). Others have reported psychopathy-related tissue reductions in the anterior, superior temporal regions (Müller et al 2008; Yang et al 2011) and the insula (de Oliveira-Souza et al 2008). In a large-scale investigation of nearly 300 adult incarcerated participants, psychopathy scores were associated with tissue reductions in the amygdala, orbitofrontal cortex, posterior cingulate, parahippocampal region, and the temporal pole (Ermer et al 2012), and these diffuse structural differences were largely replicated in a sample of juveniles with psychopathic traits (Ermer et al 2013).…”
Section: Neurobiological Models Of Psychopathymentioning
confidence: 99%